2020
DOI: 10.1371/journal.pone.0240516
|View full text |Cite
|
Sign up to set email alerts
|

Planning and optimising CHAT&PLAN: A conversation-based intervention to promote person-centred care for older people living with multimorbidity

Abstract: Background Older people are more likely to be living with cancer and multiple long-term conditions, but their needs, preferences for treatments, health priorities and lifestyle are often not identified or well-understood. There is a need to move towards a more comprehensive person-centred approach to care that focuses on the cumulative impact of a number of conditions on daily activities and quality of life. This paper describes the intervention planning process for CHAT& PLAN TM , a structured conversation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Such findings highlight variations in the fit between an individuals' needs and available services, raising questions about a "onesize-fits-all" model of healthcare. This demonstrates a need for services that are better integrated and more tailored, with care plans developed collaboratively with health serviceusers, something our ongoing work seeks to achieve [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such findings highlight variations in the fit between an individuals' needs and available services, raising questions about a "onesize-fits-all" model of healthcare. This demonstrates a need for services that are better integrated and more tailored, with care plans developed collaboratively with health serviceusers, something our ongoing work seeks to achieve [20].…”
Section: Discussionmentioning
confidence: 99%
“…As noted elsewhere [20], we planned to recruit approximately 30 participants. Despite efforts to contact several potentially eligible individuals over a period of some months, many opted not to participate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review showed that some studies are specifically dealing with GP/FM education or training to improve person-centered care (22)(23)(24). However, in most of the studies retained, personcentered care as a learning objective is usually mentioned together with other topics such as shared decision making, comprehensive approach, empowerment, compassionate care, etc.…”
Section: Person-centered Carementioning
confidence: 99%
“…(25)(26)(27)(28)(29)(30)(31). Moreover, person-centered care and these other topics are often seen as indirect objectives to be taught when organizing training programs around themes as dementia, multimorbidity, or clinical care of refugees (22)(23)(24). Gillies pleas for medical humanity as an academic discipline and resource for education (32).…”
Section: Person-centered Carementioning
confidence: 99%